2019
DOI: 10.1111/jcmm.14416
|View full text |Cite
|
Sign up to set email alerts
|

Expression of toll‐like receptors and their regulatory roles in murine cardiac telocytes

Abstract: Telocytes, newly discovered in the last decade, are interstitial cells found in numerous organs, with multiple proposed potential biological functions. Toll‐like receptors (TLRs) play an important role in innate and adaptive immunity by recognizing pathogen‐associated molecular patterns (PAMPs). However, it is still unknown whether telocytes express these innate receptors. We sought to determine the expression and role of TLRs in telocytes. In our study, we primarily detected TLR1‐9 expression in telocytes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…The TCs have an important role in the organization and control of the extracellular matrix, structural support, intercellular communication and creation of the environment . Furthermore, TCs contribute to the regulation of the Wnt pathway in regeneration and through toll‐like receptors in immunoregulation . Accordingly, patients with Crohn's disease and ulcerative colitis showed a reduced amount of TCs in affected bowel segments, as well as reduced amounts of ICCs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TCs have an important role in the organization and control of the extracellular matrix, structural support, intercellular communication and creation of the environment . Furthermore, TCs contribute to the regulation of the Wnt pathway in regeneration and through toll‐like receptors in immunoregulation . Accordingly, patients with Crohn's disease and ulcerative colitis showed a reduced amount of TCs in affected bowel segments, as well as reduced amounts of ICCs .…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, TCs contribute to the regulation of the Wnt pathway in regeneration and through tolllike receptors in immunoregulation. 19,30 Accordingly, patients with ICCs. 24,26 Although the loss of TC and ICC was parallel in inflammatory bowel diseases, 24,26 findings in diabetes mellitus showed that FLC, proven to be identical to TC, 23 were more resistant to degeneration than ICC.…”
Section: Tcs and Iccs Between The Muscle Layers Intramuscularly Anmentioning
confidence: 99%
“…However, there are much more questions refer to the mechanisms involved in TCs protection function derived from our current study: (1) the exact factors released by TCs or contained in exosomes produced by TCs; (2) the processes that TCs injection and interact with other type of cells such as epithelial cell during inflammation, whether TCs could lead to or reversing epithelial-mesenchymal transition (EMT) et al, (3) were there some other cell types, like immune cells are the target cells of the cell-cell communication of TCs, and whether the recently identified Toll-like receptors (TLR) 4 and 5/ iNOS signaling pathway were involved in this processing [31]? Therefore, the potential bio-functions of TCs in certain pathological conditions in wounds healing and mechanisms of cell-cell communication between TCs and other cells need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…TCs act as immunoregulators expressing toll-like receptors TLR 2, TLR 3, TLR 5 65 . Transfer of TCs exosomes into infarct-affected rat myocardium attenuates cardiac fibrosis, improves cardiac function, and increases angiogenesis 36 .…”
Section: Discussionmentioning
confidence: 99%